Reasoning and Rehabilitation cognitive skills programme for mentally disordered offenders: Predictors of outcome - Young, Susan (World J Psychiatry, 2016)
AIM: To investigate factors predicting treatment completion and treatment outcome of the Reasoning and Rehabilitation Mental Health Programme (R&R2MHP) cognitive skills programme for mentally disordered offenders. METHODS: Secondary analysis of data previously obtained from 97 male patients who were sectioned and detained under the United Kingdom Mental Health Act in low, medium and high security hospitals and who had completed R&R2MHP. Predictors of treatment completion included background variables and five outcome measures: Four self-reported measures of violent attitudes, social problem-solving skills, reactive anger and locus of control and an objective measure of behaviour on the ward that was completed by staff. Completion of the 16 session programme, which was delivered on a weekly basis, was classified as ≥ 12 sessions. RESULTS: It was found that the R&R2MHP is appropriate for delivery to participants of different ages, ethnic background, and at different levels of security without the completion rate or treatment effectiveness being compromised. Participants taking oral typical psychotropic medication were over seven times more likely to complete the programme than other participants. Behavioural disturbance on the ward prior to commencing the programme predicted non-completion (medium effect size). As far as treatment completion was concerned, none of the background factors predicted treatment effectiveness (age, ethnic background, level of security, number of previous convictions and number of previous hospital admissions). The best predictor of treatment effectiveness was attitude towards violence suggesting that this should be the primary outcome measure in future research evaluating outcomes of the R&R2MHP cognitive skills program. CONCLUSION: The findings suggest that a stable mental state is a key factor that predicts treatment completion.